Dialog kultur, czyli o podręczniku dla dzieci do nauczania języka polskiego jako drugiego - Achtelik, Aleksandra; Niesporek-Szamburska, Bernadeta (Postscriptum Polonistyczne, 2020)
The article is aimed at discussing the problem of teaching Polish as a foreign language to the children and teenagers of Polish origin. The authors point out to the specific situation of teaching bilingual children and present several contexts (sociocultural, intercultural, psychological and pedagogical, local) that determine the character of such teaching aid as a textbook for children who want to learn Polish as a second language. The authors of the article discuss components of such textbook and methods of preparing them using their own work (a textbook Bawimy się w polski 1) as an example. They also present certain examples of developing an inspiration (for example an intercultural one) that this textbook contains.